Implikasi Pemasaran Jasa Pendidikan Dalam Pengembangan Karakter Siswa Sekolah Dasar - Anggi Septia Nugroho; Muslim Bayar; Mashdaria Huwaina (Sekolah Tinggi Agama Islam Ma`arif Kalirejo Lampung Tengah, 2022)
Competition in the world of education is increasingly inevitable as a result of globalization. Educational marketing can be a breakthrough for problems that are a burden on the minds of an institution today. The quality of graduates is more in the spotlight in the realm of Education. Graduates are a reflection of whether or not the school where he received his education. Currently, the 2013 curriculum has developed which emphasizes character building. Graduates of schools/Educational Institutions must have a predetermined character. The 1945 Constitution explains that education must form students who, among others, believe in one God and have noble character. The purpose of this study is twofold, first to find out the implementation of marketing management of educational services in SD Muhammadiyah 1 Bandar Lampung, and second to find out its implications for the character development of students at SD Muhammadiyah 1 Bandar Lampung. The research method used is qualitative with a descriptive qualitative approach. To obtain data, researchers used observation, interviews, documentation and triangulation. While in data analysis using data reduction, data display and conclusions. Based on research using data collection and data analysis tools, the results obtained that the implications of service marketing management on the character development of students at SD Muhammadiyah 1 Bandar Lampung are as follows; 1) Exemplary, 2) Habituation, 3) Cultivating Discipline, 4) Discussion, and 5) Giving punishment.